Green Enterprise / Charlotte Charle ... [et al.] - Charles, Charlotte; Akhamat, Rasidah; Francis, Xavier; Roslan, Muhammad Haniff (2010)
Our business, Green Enterprise is a Partnership Company which registered to produce and supply environmental-friendly product. This business was planned and will be starting in the early January 2011, with our starting workers of 4 people including us as the main leader of this company. Our business will be located at Megalong Shopping Complex and production shop is at HSK Industrial area. This location is chosen due to the strategic place at the district of Penampang and the distance between two locations is about 1.6km. The recruitment process will be done by using advertisement or referral and it will be implemented for 3 months before starting the business. Our business will applied relationship marketing towards our partners, workers, potential prospect, customer, and suppliers. Our business will focused mainly on the relationship with them respectively, to maintain good long-term relationship and simultaneously selling our product altogether. Our vision is to be the premier company on producing and supplying eco-friendly product to the community of Malaysia for a healthier living environment. In addition, our main priority is to promote, educate, and spread the importance of green practice by using our product to ensure a healthier environment for everyone.